Risk diversification and vote decisions in mixed-member electoral systems - Susumu Shikano; Erik S. Herron (Public Choice, 2025)
This paper builds on the literature about mixed-member electoral systems, exploring how ballot design interacts with voter behavior. We present a theoretical model for vote decision-making in mixed-member systems that takes into account the interaction between both tiers. The model is grounded in a spatial model for vote decision-making under risk and inspired by the logic of portfolio diversification under risk. Accordingly, voters are modeled as risk-averse decision-makers who may prefer diversified vote packages (i.e. split-ticket) when party and candidate uncertainties are highly correlated. The risk diversification strategy abates when voters cast their votes sequentially. This finding provides a potential explanation for the impact of vote sequence in mixed-member systems, an under-investigated topic in the literature. It thus links the established literature on mixed-member systems with scholarship on ballot design and its effects. Additionally, the paper's analysis explores the implications of combining the proposed model with the well-established wasted vote model.
Keywords: 330; Mixed-member systems; Vote decision under uncertainty; Risk diversification; Vote sequence.